2020
DOI: 10.5588/ijtld.19.0686
|View full text |Cite
|
Sign up to set email alerts
|

Density of cigarette retailers around educational facilities in Indonesia

Abstract: BACKGROUND: With 61.4 million smokers in 2018, Indonesia makes a significant contribution to the global number of smokers. The latest data show that smoking is increasingly common in youth.OBJECTIVE: To examine the density of cigarette retailers around formal and informal educational facilities in Indonesia.METHODS: We employed geospatial and quantitative analyses using data on cigarette retailers (from surveys during July–August 2019) and educational facilities in Depok City. Data analyses, in ArcMap 10.6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Studies have shown high visibility of outdoor tobacco advertising around educational facilities in Surabaya city (East Java) and Semarang city (Central Java) (Megatsari, Ridlo, Amir, & Kusuma, 2019;Nurjanah et al, 2020). Another study has also shown a higher density of cigarette retailers around formal and informal educational facilities in Depok city (West Java) (Adisasmito et al, 2020). Moreover, we also found significant educational disparities in smoking only among women with districts in the most educated quintile had lower smoking prevalence.…”
Section: Discussionsupporting
confidence: 59%
“…Studies have shown high visibility of outdoor tobacco advertising around educational facilities in Surabaya city (East Java) and Semarang city (Central Java) (Megatsari, Ridlo, Amir, & Kusuma, 2019;Nurjanah et al, 2020). Another study has also shown a higher density of cigarette retailers around formal and informal educational facilities in Depok city (West Java) (Adisasmito et al, 2020). Moreover, we also found significant educational disparities in smoking only among women with districts in the most educated quintile had lower smoking prevalence.…”
Section: Discussionsupporting
confidence: 59%
“…Our study is in line with a study in Thailand that reported tobacco retailers were more densely located around schools 18 and a study in Depok, Indonesia that reported a 40% higher density of cigarette retailers in areas closer to educational facilities. 14…”
Section: Discussionmentioning
confidence: 99%
“…25,26 As an example, a proposal to ban cigarette sales within 100 m from schools is currently with the Sri Lankan parliament as an amendment to the National Authority on Tobacco and Alcohol Act 2006. 14 A study in India recommended tobacco sales ban near educational institutions to be expanded beyond 100 m to reduce retailer density. 19 A study in Bali also suggests a tobacco sales ban within 500 m from facilities, as it may deliver the greatest impact on reducing smoking prevalence among adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on schools, including addresses, were obtained from Riyadh General Directorate of Education and the Ministry of Education. We used Google Sheets and geocoding add-ons to convert each facility address into geocodes (latitude and longitude) [ 16 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%